Kinematic strength predictors at the shoulder in youth baseball pitchers - Hadro, A.; Fehr, S.; Butler, B.; Apolinario, M.; Damrow, D.; Liu, X. C. (Journal of Exercise, Sport & Orthopedics, 2019)
The number of throwing-related arm injuries in youth baseball pitchers is increasing. Many variables correlate with increased injury rates, but the role of shoulder strength in pitching mechanics and resulting injuries is not well understood. Thus, the purpose of this study was [1] determine if shoulder strength is associated with youth pitchers` throwing kinematics, [2] investigate how Biodex can be used as a training modality for improving strength and performance while preventing throwing-related injuries. Kinematic data was collected from seventeen youth pitchers ages 9-14 years old. Isometric and isokinetic strength data was collected using the Biodex. Spearman correlations were used to investigate associations between Biodex measurements and kinematic data at the shoulder for maximum external rotation (MER), maximum internal rotation (MIR), maximal internal acceleration (MIA), and maximal internal velocity (MIV) during the pitching cycle. There was a significant correlation between MER and isokinetic external rotation strength at 60 and 180°/sec and isometric external and internal rotation at 45°. MIA was significantly correlated with isokinetic external and internal rotation strength at 60°/sec, and isometric internal rotation strength at 0, 45, and 105°. MIV was significantly correlated with isokinetic external and internal rotation strength at 60°/sec. Age, BMI, and years of experience were investigated as confounding variables; none were significant. There are significant correlations between kinematic measurements during the pitching cycle and shoulder strength. We feel training at strength parameters best correlated with each kinematic phase could improve pitching mechanics while preventing injuries in youth pitchers.